ECO-THEOLOGY OF SEYYED HOSSEIN NASR'S THOUGHT AND IT’S RELEVANCE ON THE AWARENESS FOR ENVIRONMENTAL MANAGEMENT IN UIN WALISONGO CAMPUS - wahib Bahtiar; Luthfi Rahman; Makmur Aji (UIN Sunan Kalijaga Yogyakarta, 2026)
This study aims to analyze how Seyyed Hossein Nasr’s ecological theology can be used as a conceptual framework for understanding and responding to the crisis of spiritual awareness in environmental management at UIN Walisongo Campus. The study employs a qualitative approach by combining a literature review of Seyyed Hossein Nasr’s primary works and contemporary academic literature (2020–2024), along with semi-structured interviews involving four informants consisting of two campus environmental managers and two students selected purposively. Primary works such as The Encounter of Man and Nature: The Spiritual Crisis of Modern Man and Religion and the Order of Nature serve as the main foundations for understanding the concepts of the sacredness of nature, humans as khalifah (stewards), and critiques of secularism that reduce nature to an object of exploitation. The analysis reveals that the environmental conditions on campus—reflected in the low awareness of environmental preservation, inadequate maintenance of green areas, and poor waste management—represent a deeper problem in which spirituality, metaphysical values, and religious perspectives toward nature are neglected within campus activities. Interviews indicate that most academics perceive environmental issues merely as administrative and technical matters, such as cleaning, gardening, and waste management, without considering spiritual values. Supporting literature, including recent articles such as “Ethics Toward Nature in the Ecosophy of Seyyed Hossein Nasr” (2023) and “Seyyed Hossein Nasr: An Islamic Critique of Environmental Secularism” (2024), reinforces the view that the modern secular paradigm is the primary cause of the ecological crisis. Consequently, there is an urgent need to restore spirituality within the relationship between humans and nature as part of environmental conservation efforts. These findings lead to the conclusion that environmental management on campus, particularly through the integration of theological-ecological values, is highly important. Environmental education should be designed through a spiritual approach that instills an understanding that nature is a sacred creation and that humans, as khalifah, bear the responsibility to preserve it, so that the campus becomes not only physically clean but also spiritually conscious. The implementation of these recommendations includes integrating environmental values into the curriculum, developing spirituality-based environmental awareness, establishing environmentally conscious communities with a spiritual focus, and reviewing campus policies to integrate Islamic ecological ethics. This study concludes that Nasr’s thought is not only theoretically relevant but can also function as a practical normative foundation for transforming campus environmental culture by strengthening the spiritual awareness and ecological commitment of the academic community. Keywords: ecological theology, Seyyed Hossein Nasr, spiritual awareness, campus environment, UIN Walisongo, ecosufism Penelitian ini bertujuan untuk menganalisis bagaimana pemikiran teologi ekologi Seyyed Hossein Nasr dapat digunakan sebagai kerangka konseptual dalam memahami dan merespons krisis kesadaran spiritual dalam pengelolaan lingkungan Kampus UIN Walisongo. Penelitian ini menggunakan pendekatan kualitatif dengan mengombinasikan studi pustaka atas karya-karya primer Seyyed Hossein Nasr dan literatur akademik kontemporer (2020–2024), serta wawancara semi-terstruktur dengan 4 informan yang terdiri atas 2 pengelola lingkungan kampus dan 2 mahasiswa, yang dipilih secara purposif. Karya primer seperti The Encounter of Man and Nature: The Spiritual Crisis of Modern Man dan Religion and the Order of Nature dijadikan pijakan utama untuk memahami konsep sakralitas alam, manusia sebagai khalifah, dan kritik terhadap sekularisme yang mereduksi alam menjadi objek eksploitasi. Analisis mengungkapkan bahwa situasi lingkungan di kampus yang terlihat dari rendahnya kesadaran mengenai pelestariannya, perawatan area hijau, serta pengelolaan sampah merefleksikan masalah yang lebih mendalam, di mana aspek-aspek seperti spiritualitas, nilai-nilai metafisik, dan agama terhadap alam diabaikan dalam aktivitas kampus. Wawancara menunjukkan bahwa sebagian besar akademisi memandang lingkungan hanya sebagai isu administratif dan teknis (seperti pembersihan, berkebun, dan pengelolaan limbah), tanpa adanya pertimbangan nilai-nilai spiritual. Tinjauan pustaka yang mendukung, seperti artikel terkini berjudul “Etika Terhadap Alam dalam Perspektif Ekosofi Seyyed Hossein Nasr” (2023) dan “Seyyed Hossein Nasr: Kritikan Islam terhadap Sekularisme Lingkungan” (2024) memperkuat pandangan bahwa paradigma sekuler modern merupakan penyebab utama krisis ekologi. Sebagai akibatnya, terdapat kebutuhan mendesak untuk mengembalikan spiritualitas dalam hubungan antara manusia dan alam demi upaya pelestarian. Penemuan ini mengarah pada kesimpulan bahwa pengelolaan lingkungan di kampus, dalam hal ini pengintegrasian nilai-nilai ekologi teologis, adalah sangat penting. Pendidikan lingkungan harus disusun dengan pendekatan spiritual menanamkan pemahaman bahwa alam adalah ciptaan yang suci, dan bahwa manusia sebagai khalifah memiliki tanggung jawab untuk menjaga sehingga kampus tidak hanya bersih secara fisik, tetapi juga bersih secara spiritual. Pelaksanaan dari saran tersebut meliputi: penggabungan nilai-nilai kurikulum lingkungan, pengembangan spiritualitas, pembentukan komunitas yang peduli terhadap lingkungan dengan fokus spiritual, serta peninjauan kembali kebijakan kampus untuk mengintegrasikan etika ekologis Islam. Penelitian ini menyimpulkan bahwa pemikiran Nasr tidak hanya memiliki relevansi sebagai sebuah teori, tetapi juga dapat berperan sebagai landasan normatif praktis untuk mengubah budaya lingkungan kampus dengan memperkuat kesadaran spiritual serta komitmen ekologis dari komunitas akademik. Kata kunci: teologi ekologi, Seyyed Hossein Nasr, kesadaran spiritual, lingkungan kampus, UIN Walisongo, ekosufisme.